Semantic Bridging in Sharia Financial Literacy: A Culturally Grounded Communication Model for MSMEs in Palu City - Taufik; M Hidayat (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2026)
This study develops a contextual communication model that integrates Kaili cultural values with Islamic principles particularly ash-shaffafiyyah (transparency) to strengthen Sharia-based financial literacy among Muslim MSMEs in Palu City. Addressing a critical gap in existing financial literacy programs that prioritize technical instruction while neglecting socio-cultural meaning systems, this research employs a qualitative ethnographic communication approach. Data were collected over six months through participant observation, document analysis, and in-depth interviews with 18 informants, including MSME actors, community leaders, and religious figures. Data credibility was ensured through triangulation and member checking, followed by thematic analysis. The findings indicate that barriers to Sharia financial literacy stem not from limited information access, but from misalignment between formal Sharia discourse and the symbolic-cultural meanings embedded in Kaili social life, producing semantic noise. To address this gap, the study introduces the concept of semantic bridging, defined as a communicative process that aligns local values nosarara nosabatutu (brotherhood) and lenodafa (honesty) with Sharia transparency principles. The proposed model comprises three stages. The first, dialectical mapping and communal validation of cultural meanings. The second, epistemic internalization through reflective dialogue and mentoring, and third symbolic mediation via culturally resonant language and symbols. This model provides an operational framework for local governments, Islamic financial institutions, and community-based facilitators to design participatory, culturally grounded Sharia financial literacy interventions at the community and municipal policy levels.